1998
DOI: 10.1117/12.309560
|View full text |Cite
|
Sign up to set email alerts
|

High-power extreme-ultraviolet source based on gas jets

Abstract: We report on the development of a high-power laser plasma extreme ultraviolet (EUV) source for Extreme Ultraviolet Lithography. The source is based on the plasma emission of a recycled jet beam of large Xe clusters and produces no particulate debris. The source will be driven by a pulsed laser delivering 1500 W of focused average power to the cluster jet target. To develop condensers and to optimize source performance, a low-power laboratory cluster jet prototype has been used to study the spectroscopy, angula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…This power will give rise to severe heating of mechanical details in the vicinity of the plasma due to re-emitted and scattered out-of-band radiation as well as energetic ions and atoms. It has also been shown that the plasma will erode mechanical parts such as a nozzle in the vicinity of the plasma, 14 and that the material eroded will damage the sensitive condenser optics, thereby limiting the mirror life time. This problem will be even worse in discharge plasmas.…”
Section: Long Working Distancementioning
confidence: 99%
“…This power will give rise to severe heating of mechanical details in the vicinity of the plasma due to re-emitted and scattered out-of-band radiation as well as energetic ions and atoms. It has also been shown that the plasma will erode mechanical parts such as a nozzle in the vicinity of the plasma, 14 and that the material eroded will damage the sensitive condenser optics, thereby limiting the mirror life time. This problem will be even worse in discharge plasmas.…”
Section: Long Working Distancementioning
confidence: 99%
“…In the initial implementation, a cluster jet target [5][6] based upon the supersonic expansion of gaseous Xe into a vacuum was used in conjunction with a 40W Coherent Infinity Nd:YAG laser. During the past year, the source has been upgraded to a 1500W TRW laser (replacing the 40W Coherent Infinity laser) and the Xe cluster jet has been replaced with a liquid Xe spray jet target.…”
Section: Illuminator Subsystemmentioning
confidence: 99%
“…Recently, laser-produced plasma x-ray sources have been highlighted as one of the most reliable sources for extreme ultraviolet lithography (EUVL). Intensive research has been performed in this field [3][4][5]. On the other hand, laser-plasma x-ray sources have been investigated for many other applications such as x-ray microscopy [6] and absorption spectroscopy [7,8].…”
Section: Introductionmentioning
confidence: 99%